Konstruksi Legitimasi dan Akibat Perkawinan Dibawah Tangan: Mengulang Kawin atau Itsbat Nikah? - Umar Haris Sanjaya; Putri, Dita Fadillah (Fakultas Hukum Universitas Islam Indonesia, 2024)
This study brings forward the analysis for the topic of underhanded marriage and the potential for it to be followed up by itsbat nikah or reconducting the marriage process with the same partner, thus undertaking a second marriage with registration. Each of these options poses different legal consequences, especially for the child that has been born, in which they carry the possibility to become a legitimate child or vice versa. This study raises the issue of how the construction of legitimacy and the validity of underhanded marriages; as well as whether the legitimacy of underhanded marriages is carried out with itsbat nikah or repetition of the marriage process. The method used is normative legal research through the statutory approach and the conceptual approach with qualitative analysis. The study concludes that in repeating a marriage process where the first one was conducted underhandedly then retaken and recorded, consequently means that only the the second marriage that is to be considered valid. Therefore, it does not apply retroactively to the previous marriage which makes the proper construction to be carried out is to simply perform itsbat nikah. Second, the status of a child born from an underhanded marriage will only be valid if the said itsbat nikah is carried out, but if the marriage process is repeated without, then the status of the child remains invalid due to the non-retroactive nature in the legitimacy of the marriage.Keywords: Itsbat Nikah, Repetition of Marriage Process, Underhanded Marriage. AbstrakPenelitian ini bertujuan untuk menganalisis topik tentang perkawinan dibawah tangan seseorang potensi dapat ditindaklanjuti dengan itsbat nikah ataupun mengulang proses perkawinan kembali dengan pasangan yang sama atau melakukan perkawinan kedua dengan pencatatan. Kedua pilihan tersebut masing-masing memiliki akibat hukum yang berbeda terutama pada anak yang dilahirkan, sehingga berpotensi menjadi anak sah ataupun kebalikannya. Penelitian ini mengangkat permasalahan bagaimana konstruksi legitimasi terhadap keabsahan perkawinan dibawah tangan dan apakah legitimasi perkawinan dibawah tangan dilakukan dengan itsbat nikah atau mengulang proses kawin. Metode penelitian yang digunakan adalah hukum normatif melalui pendekatan pendekatan peraturan perundang-undangan dan konseptual dengan analisa kualitatif. Penelitian menyimpulkan bahwa melakukan pengulangan perkawinan dimana yang pertama dibawah tangan lalu diulang kembali dan dicatatkan menjadikan perkawinan yang dianggap sah adalah perkawinan yang kedua, artinya tidak berlaku surut terhadap perkawinan sebelumnya sehingga konstruksi yang tepat adalah tinggal melaksanakan itsbat nikah. Kedua, status anak yang lahir dari perkawinan dibawah tangan akan menjadi sah bila perkawinan tersebut dilakukan itsbat nikah, tetapi bila diulang perkawinannya justru menjadi tidak sah karena legitimasi perkawinannya tidak berlaku surut yang turut berdampak pada status anak yang dilahirkan.Kata Kunci: Itsbat Nikah, Mengulang Kawin, Perkawinan Dibawah Tangan.